2014
DOI: 10.1021/jm401616g
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Modulators Informed by Crystallography Lead to a New Rationale for Receptor Selectivity, Function, and Implications for Structure-Based Design

Abstract: The structural basis of the pharmacology enabling the use of glucocorticoids as reliable treatments for inflammation and autoimmune diseases has been augmented with a new group of glucocorticoid receptor (GR) ligands. Compound 10, the archetype of a new family of dibenzoxepane and dibenzosuberane sulfonamides, is a potent anti-inflammatory agent with selectivity for the GR versus other steroid receptors and a differentiated gene expression profile versus clinical glucocorticoids (lower GR transactivation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…and modelling revealed a second binding site within the ligand-binding pocket of GR (Biggadike et al, 2009). Also the crystal structure of GR-LBD bound with compound 10, which retains full transrepression with a partial transactivation ability, shows a new binding mode, clearly different from the classic GC binding model (Carson et al, 2014). The potential binding of SEGRMs to other transcriptional isoforms besides the classical GRα remains an uncharted area.…”
Section: Structure Of Glucocorticoid Receptorsmentioning
confidence: 96%
See 2 more Smart Citations
“…and modelling revealed a second binding site within the ligand-binding pocket of GR (Biggadike et al, 2009). Also the crystal structure of GR-LBD bound with compound 10, which retains full transrepression with a partial transactivation ability, shows a new binding mode, clearly different from the classic GC binding model (Carson et al, 2014). The potential binding of SEGRMs to other transcriptional isoforms besides the classical GRα remains an uncharted area.…”
Section: Structure Of Glucocorticoid Receptorsmentioning
confidence: 96%
“…With regards to the latter, the anti-inflammatory effects of the test SEGRMs were assessed using inflammatory disease models in vivo, such as allergic conjunctivitis (Baiula et al, 2014), (rheumatoid) arthritis Dewint et al, 2008;López et al, 2008;Thiele et al, 2012;Rauner et al, 2013;Carson et al, 2014), neuro-inflammation (Zhang et al, 2009a;van Loo et al, 2010), asthma (Reber et al, 2012) and colitis (Reuter et al, 2012a,b). Yet, it needs to be said that, although it has been proven that all SEGRMs discussed here (except PF-802) can bind to GR (Coghlan et al, 2003;Schacke et al, 2004Schacke et al, , 2009De Bosscher et al, 2005;Chivers et al, 2006;Miner et al, 2007;Zhang et al, 2009b;van Lierop et al, 2012;Brandish et al, 2014;Carson et al, 2014), only CpdA and ZK 216346 are shown to elicit a partial or full nuclear translocation of GR (De Bosscher et al, 2005;Dewint et al, 2008;Yemelyanov et al, 2008;Robertson et al, 2010;Reuter et al, 2012b;Presman et al, 2014;Drebert et al, 2015) (also see 2.1 Structure of Glucocorticoid receptors). Therefore, it cannot be completely excluded that their observed in vitro and in vivo anti-inflammatory effect is perhaps (partially) mediated by GR-independent action mechanisms.…”
Section: Selective Glucocorticoid Receptor Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes antagonist data for several analogues compared to MIF in HEK cells transfected with functional GR and the tyrosine amino transferase (TAT) assay run in H4−II E cells. 36 The indole sulfonamides were ∼10× less potent than the reference steroid, yet most analogues were more selective than MIF. In this instance, the size of the indole R 2 substituent shows a trend toward improved antagonism.…”
Section: ■ Resultsmentioning
confidence: 98%
“…In this instance, the size of the indole R 2 substituent shows a trend toward improved antagonism. (Compounds 8,15,16,18,and 19 were also assayed in models of GR agonism and transrepression where they did not show significant activity 36 (Supporting Information Table S1)).…”
Section: ■ Resultsmentioning
confidence: 99%